La gestión del talento humano y su incidencia en el desempeño laboral de los servidores públicos del Gobierno Autónomo Descentralizado Municipal del cantón Chone - Arteaga Muñoz, María Alexandra (2023)
Human talent is the most important resource in the administrative, operational and service management of an organization, and in this context, the research aims to determine the incidence of human talent management in the work performance of public servants of the Autonomous Decentralized Municipal Government of the Chone canton, for which a descriptive-correlational investigation was developed to find out if one variable is affecting the other, under a qualitative approach, through inductive, analytical and synthetic methods, using tools such as the interview , the survey, the field and bibliographical research, it was obtained as a result that the Municipal GAD of Chone, does not have an approved process manual, does not have a manual of functions or approved job profiles, which is why the technical administration of human talent does not comply with the legal and regulatory standards that the Organic Law of Public Service and its regulations impose, therefore they do not carry out performance evaluations of their employees. This investigation proposes, according to the methodology and matrices of the Ministry of Labor, to carry out performance evaluations, and proposed an example of the same in the Accounting Coordination, where the results were satisfactory, leaving in evidence that, despite the shortcomings in the technical administration of human talent, the servers do have good job performance